2018
DOI: 10.1111/1753-6405.12722
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐demographic factors drive regional differences in participation in the National Bowel Cancer Screening Program – An ecological analysis

Abstract: A ustralia performs exceptionally well in improving the overall survival of people diagnosed with cancer. 1 However, advances in early detection and treatment of cancer may not benefit all Australians equally. Significant disparities in health outcomes -including cancer mortality -continue to exist, most notably among people living in rural, regional and remote areas of Australia and Indigenous Australians. 2-4Colorectal cancer (CRC) or bowel cancer is the most common cancer for men and women combined and is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
2
15
1
Order By: Relevance
“…Educational, financial, and social disadvantage can often result in depleted resources for leading a healthy lifestyle and addressing health issues ( 33 35 ). Our findings support a growing body of recent evidence suggesting that regional disparity in health may be less about location and more about the characteristics of people within a geographic region ( 36 38 ). Recently, health researchers have suggested a shift in focus from broad urban-rural health disparities to understanding the unique characteristics of different communities and the individuals within them ( 36 , 39 , 40 ).…”
Section: Discussionsupporting
confidence: 87%
“…Educational, financial, and social disadvantage can often result in depleted resources for leading a healthy lifestyle and addressing health issues ( 33 35 ). Our findings support a growing body of recent evidence suggesting that regional disparity in health may be less about location and more about the characteristics of people within a geographic region ( 36 38 ). Recently, health researchers have suggested a shift in focus from broad urban-rural health disparities to understanding the unique characteristics of different communities and the individuals within them ( 36 , 39 , 40 ).…”
Section: Discussionsupporting
confidence: 87%
“…Although Indigenous status was associated with poorer performance in many of the health system indicators examined, the associations were likely to be due to the socioeconomic disadvantage that is experienced by Indigenous peoples. For example, a previous Australia‐wide study found that lower participation in bowel cancer screening in remote areas was partly related to low uptake by Indigenous Australians, although the results did not hold true for a NSW subgroup analysis 9 . In the current study, remoteness and socioeconomic disadvantage were the strongest predictors of low participation.…”
Section: Discussioncontrasting
confidence: 82%
“…Such an approach masks heterogeneity in rural areas in terms of health status, health care and the social and demographic profile of the population, thereby restricting the tailoring of the provision of services relevant to the needs of the local population. For example, a study of 504 local government areas (LGAs) in Australia found sociodemographic characteristics, particularly Indigenous status, cultural background and population age structure, were more important predictors of geographic disparities in bowel cancer screening participation than remoteness 9 …”
Section: Introductionmentioning
confidence: 99%
“…An interesting result that we found with the use of data at the municipality level is that more men in the screening population were associated with a higher organised screening coverage. This finding seemed counter-intuitive at first sight, since previous studies have shown that women are more likely to participate in CRC screening than men [8,20,23,[29][30][31]. However, a closer data inspection revealed that in Flanders, within a municipality, the screening coverage in women was higher compared to men, but among municipalities, more men in the screening population were associated with a higher screening coverage in both men and women, leading to a higher overall screening coverage.…”
Section: Discussionmentioning
confidence: 80%